Investigating the most essential skills of planners in Ethiopia's Amhara National Regional State's Regiopolitan cities - Nigatu Amsalu Workineh (Journal of Innovation and Entrepreneurship, 2022)
This study intends to answer the specific skills and skills Ethiopian planners, particularly Amhara National Regional State's Regiopolitan cities planners, require the most in their urban planning profession. In today's urban world, understanding city dynamics, forecasting and predicting vibrant cities, making urban planning decisions and putting them into practice, collaborating with stakeholders from various governments and educational backgrounds, persuading people to accept urban plans, and building good personal and skilled relationships have all become highly complex and challenging. As a result, to succeed in their jobs in Ethiopia, planners must possess particular skills. This study looks into the essential skills that planners require in today's dynamic and complex urban environment. The investigation was conducted in Ethiopia as part of a more extensive regional study of Regiopolitan cities. A structured questionnaire survey of 104 experienced planners was undertaken, and semi-structured in-depth interviews with 9 key informants to investigate the essential planners' skills in the Ethiopian planning system to find the essential skills needed in practice. The findings demonstrate that an urban planning method in Regiopolitan cites of Amhara National Regional State, Ethiopia urban planning system is such practical planners who wish to carve out a position for them must equip themselves with analytical and synthesis skills. Finally, the study included recommendations for improving planners' future skills and more research into the matter.
Keywords: 650; Cities; Ethiopia; Planners; Skills; Urban